Southern African agriculture and climate change: A comprehensive analysis - Mozambique - Maure, Genito A.; Bila, Silena; Sibanda, Lindiwe M.; Thomas, Timothy S. (International Food Policy Research Institute, 2012)
Mozambique s diverse climate is influenced by monsoons from the Indian Ocean and the hot current of the Mozambique Canal. The country s location makes it particularly vulnerability to climatic hazards such as drought, floods, and recurring tropical cyclones during the rainy season, which spans from October to April. Agriculture is the major activity of most of the population, contributing about 24 percent of the country s gross domestic product. The major crops are sugarcane, copra, sesame seeds, sugar beans, sunflower, rice, millet, and maize. Mozambique s population has doubled from independence in 1975 to the present day. The mortality rate among children under five has declined in the last 40 years thanks to improvements in the quality of health services and wider access to those services, mainly in rural areas. Life expectancy at birth increased from the 1960s through the late 1990s, but in the recent years it has decreased.